PERSPECTIVE AND ESSENCE OF ACHIEVEMENT MOTIVATION TO PURSUE LEARNING OUTCOMES - ., Wahyudi . (Universitas Tanjungpura, 2019)
The dimensions of students’ achievement consist of various factors. These factors include completeness of school infrastructure, attention from parents, study habits, and achievement motivation. From several studies conducted by researchers in the field of education, it was found that achievement motivation factors had a greater contribution than other factors. Therefore, a teacher needs to know the needs of students to pursue their learning achievement. With this good understanding, the teacher can look for various efforts to grow motivation in accordance with the diversity or characteristics of the students.